Cloud Computing And Security Issues In The Cloud (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Cloud computing has formed the conceptual and infrastructural  basis for tomorrow’s computing. The global computing  infrastructure is rapidly moving towards cloud based architecture.  While it is important to take advantages of could based computing  by means of deploying it in diversified sectors, the security aspects  in a cloud based computing environment remains at the core of  interest. Cloud based services and service providers are being  evolved which has resulted in a new business trend based on  cloud technology. With the introduction of numerous cloud based  services and geographically dispersed cloud service providers,  sensitive information of different entities are normally stored  in remote servers and locations with the possibilities of being  exposed to unwanted parties in situations where the cloud servers  storing those information are compromised. If security is not  robust and consistent, the flexibility and advantages that cloud  computing has to offer will have little credibility. This paper  presents a review on the cloud computing concepts as well as  security issues inherent within the context of cloud computing and  cloud infrastructure.
Keywords: Cloud computing; cloud service; cloud security; computer network; distributed computing, security